Rapid eye movement sleep behavior disorder and rapid eye movement sleep without atonia are more frequent in advanced versus early Parkinson's disease. Issue 9 (15th March 2021) - Sringean, Jirada; Stefani, Ambra; Marini, Kathrin; Bergmann, Melanie; Werkmann, Mario; Holzknecht, Evi; De Marzi, Roberto; Brandauer, Elisabeth; Hackner, Heinz; Djamshidian, Atbin; Stockner, Heike; Gaig, Carles; et al.
Abstract: Study Objectives: To evaluate macro sleep architecture and characterize rapid eye movement (REM) sleep without atonia (RWA) by using the SINBAR excessive electromyographic (EMG) montage including mentalis and upper extremity muscles in early and advanced Parkinson's disease (PD). Methods: We recruited 30 patients with early- and advanced-stage of PD according to Movement Disorder Society (MDS) Clinical Diagnostic Criteria. Participants were classified as early-stage PD if they were treatment-naïve or had no motor complications and had been diagnosed with PD within the previous 6 years. Advanced PD was defined as a disease duration equal to or >6 years with or without motor complications. Results: There was significantly shorter REM sleep latency in early as compared to the advanced stage of PD. We found that the sleep Innsbruck Barcelona (SINBAR) EMG index and tonic EMG activity of the mentalis muscle in advanced-stage PD were significantly higher than in early-stage PD with a trend in phasic EMG activity of the flexor digitorum superficialis muscles. The SINBAR EMG index, tonic and any EMG activity of the mentalis muscle, and phasic EMG activity of flexor digitorum superficialis muscles significantly correlated with disease duration. Conclusions: This study analyzed RWA using the SINBAR EMG montage in early- and advanced-stage of PD and showed higher RWA in mentalis and flexor digitorum superficialis muscles and SINBAR EMG index in advanced-PD patients compared to patients in the early stage. Also, polysomnography-confirmed REM sleep behavior disorder was more common in advanced versus early-stage patients. Our findings suggest that RWA worsens or is more intense or more frequent with disease progression.